2018
DOI: 10.1080/1354750x.2018.1443513
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of DNA damages in lymphocytes of agricultural workers exposed to pesticides by comet assay in a cross-sectional study

Abstract: The adjusted associations (ORs) between the comet parameters and exposure to pesticides were significant. The sensitivity of the comet test was low (41%), the specificity (89%) and the predictive positive value (0.77) were found acceptable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 75 publications
0
15
0
1
Order By: Relevance
“…In this context, due to the often unknown environmental exposure to asbestos, low price biomarkers of exposure are needed [56][57][58][59] for the ascertainment of environmental exposure and the early prevention of health effects. From this point of view, a new frontier can be represented by the use of the comet assay [60][61][62][63] since inhaled asbestos may induce oxidative stress and biochemical changes in lipids, proteins, DNA and RNA [18].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, due to the often unknown environmental exposure to asbestos, low price biomarkers of exposure are needed [56][57][58][59] for the ascertainment of environmental exposure and the early prevention of health effects. From this point of view, a new frontier can be represented by the use of the comet assay [60][61][62][63] since inhaled asbestos may induce oxidative stress and biochemical changes in lipids, proteins, DNA and RNA [18].…”
Section: Discussionmentioning
confidence: 99%
“…Author details 1 Department of Dermatology, University AllergyCentre, Medical Faculty Carl Gustav Carus, Technical University Dresden, Fetscherstr 74, D-01307 Dresden, Germany. 2 Centre of Evidence-based Healthcare, University Hospital and Medical Faculty Carl Gustav Carus, Technical University Dresden, Dresden, Germany. 3 Institute and Policlinic for Occupational and Social Medicine, Faculty of Medicine Carl Gustav Carus, Dresden, Germany.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…Outdoor workers are exposed to many different hazards like solar ultraviolet (UV) radiation and heat, pesticides and other chemicals as well as urban air pollutants and allergens that may lead to health problems [1][2][3][4]. This article focuses on solar UV radiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The coke oven workers had a significantly higher risk of DNA damage than did the controls, and dose-response relationships were also found between external exposure (exposure category) or internal doses (urinary 1-hydroxypyrene) and DNA damage [29]. Aberrant DNA methylation is one of the best-known epigenetic changes in human cancers and healthy subjects exposed to carcinogens [30,31]. Another report found that urinary PAH metabolites were significantly elevated in coke oven workers.…”
Section: Biomarkers and Coke Oven Workersmentioning
confidence: 99%